Optimal fiscal policy with utility-enhancing government spending, consumption taxation and a common income tax rate: the case of Bulgaria - Aleksandar Vasilev (Review of Economics, 2018)
This paper explores the e ffects of fi scal policy in an economy based on indirect taxes, and one that is constrained to taxing all (labor and capital) income at the same rate. The focus of the paper is on the relative importance of consumption vs. income taxation, as well as on the provision of utility-enhancing public services. To this end, a Real-Business-Cycle model, calibrated to Bulgarian data (1999-2014), was set up with a richer public finance side. Bulgarian economy was chosen as a case study due to its major dependence on consumption taxation as a source of tax revenue. To illustrate the e ffects of fiscal policy, two regimes were compared and contrasted to one another - exogenous vs. optimal (Ramsey) policy case. The main fi ndings from the computational experiments performed are: (i) The optimal steady-state (capital and labor income) tax rate is zero, as it is the most distortionary tax to use; (ii) The optimal steady-state consumption tax (the only source of revenue) has to almost double to finance the optimally-set level of government purchases.
Keywords: D58; 330; consumption tax; income tax; general equilibrium; fiscal policy